Features of endodontic treatment of teeth in elderly patients before prosthodontics (Эндодонтия Today)
This paper describes the features of endodontic interventions in elderly patients, allowing to exclude complications of the general condition of the body associated with prolonged forced position of the patient in the dental chair, and provide quality care. It is considered appropriate to reduce this category of patients, duration of endodontic interventions and increase the number of visits. The use of dosed electrophoresis (depophoresis) by Knappvost to avoid infection of the root canal and improve the quality of endodontic treatment. Security of endodontic treatment of teeth in elderly patients contributes to the use of amide anesthetics for pain relief without the vasoconstrictor and in reduced amount.